The Destruction of a Great Idea: Public Education and the Politics of Instrumentalism. Issue 3 (28th November 2022) - Säfström, Carl Anders
Abstract: This article explores the erosion of public education as a project of democratization. It locates this erosion in the neoliberal world order that has redefined our understanding of schooling the democratic citizen in terms of developing market assets. In it, Carl Anders Säfström investigates specifically how this shift is apparent in the ways in which schooling operates and demonstrates how education itself stands in stark contrast to this view of schooling's function. The need to revitalize education and teaching as means to further equality in society derives from the inequality that neoliberal schooling produces and that is undermining the democratic character of reputedly democratic orders. Teaching liveable life, Säfström concludes, means to verify equality in situations otherwise defined by inequality and, by this means, to expand who can be seen as belonging to democratic public life. His critique of political instrumentalism shows how late capitalism's neoliberal market ideology is systematically linked with schooling and results in the institutionalization of this ideology.